Flood Events in Gangapur Village, Banke District: An Example of Climate Change-induced Disaster in Nepal - Bhattarai, Tara Nidhi (Journal of Institute of Science and Technology, 2015)
Climate change impacts in Nepal have resulted, among others, localized downpour which may trigger severe flooding and associated disasters in some parts of the country, particularly in the southern slope of the Siwalik. The purpose of this investigation was to evaluate the consequences of climate change impacts in the Dhondra River watershed that covers southern slope of the Siwalik and northern part of the Terai plane in Banke district, western Nepal. For the purpose, a field investigation was carried out and it indicated that Ward Nos. 5 and 6 of Gangapur Village Development Committee (VDC) were inundated in 2000 due to the blockade of the Singhya River by the deposition of flood-driven sediments brought by the Dhondra River. Consequently, about 305 families were completely displaced due to the inundation in and around their home and farmlands. The flood was resulted due to a localized torrential rainfall in Dhondra River's upper reaches in the Siwalik area. Following the year 2000, the Dhondra River started depositing sandy sediments in and around the confluence point with the Singhya River during each monsoon seasons. This paper briefly summarizes the causes of the disaster and its consequences to the displaced people, and surrounding geo-environment. Journal of Institute of Science and Technology, 2014, 19(1): 79-85